2013
DOI: 10.1038/srep01848
|View full text |Cite
|
Sign up to set email alerts
|

DEVD-Based Hydrogelator Minimizes Cellular Apoptosis Induction

Abstract: Herein, we report the rational design of a DEVD-based heptapeptide hydrogelator 1 which is susceptible to caspase-3 (CASP3), and its isomeric control hydrogelator 2 with a DEDV-based heptapeptide sequence. Self-assembly of 1 in water results in flexuous, long nanofibers to form supramolecular hydrogel I with higher mechanical strength than that of hydrogel II which is composed of rigid, short nanofibers of 2. In vitro enzymatic analysis indicated that 1 is susceptive to CASP3 while 2 is not. 3-(4,5-dimethylthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Inhibition of cancer cells (breast cancer cell line, MCF7) proliferation was evaluated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction. 64 MCF-7 cells were seeded at a density of 10 000 cells per well in a 96-well plate for 18−24 h before treatment with the hydrogelator. Then cells were treated with various concentrations of the compound (stock concentration was 10 mM in autoclaved water) in DMEM medium containing 10% fetal bovine serum for 24h in 96-well plate (Figure 9).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Inhibition of cancer cells (breast cancer cell line, MCF7) proliferation was evaluated by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction. 64 MCF-7 cells were seeded at a density of 10 000 cells per well in a 96-well plate for 18−24 h before treatment with the hydrogelator. Then cells were treated with various concentrations of the compound (stock concentration was 10 mM in autoclaved water) in DMEM medium containing 10% fetal bovine serum for 24h in 96-well plate (Figure 9).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Western blot analysis indicated that the isomer 474 , which is not a substrate of caspase-3, at 400 μM, obviously is able to activate caspase-3 to induce cell death via apoptosis. 985 …”
Section: Applicationsmentioning
confidence: 99%
“…Because it is easy to observe sol–gel phase transition, the use of enzymes to trigger the formation of supramolecular hydrogels becomes a facile assay to identify the substrates for ENS. Some of those examples ,, have been summarized in a recent review on supramolecular hydrogels . The following section mainly discusses the works published after that review according to the types of the enzymes.…”
Section: Enzymatic Noncovalent Synthesis In Cell-free Conditionsmentioning
confidence: 99%